DEVELOPMENT OF SIAPAJAR AS A TECHNOLOGY-BASED SYSTEM FOR TEACHER ADMINISTRATION MANAGEMENT - Haq, Muh. Dliyaul; Niron, Maria Dominika; Sukinawan, Kiki; Indra Jaya, Nugroho Prima; Zein, Achmad Sjarifudin (JURNAL EDUSCIENCE, 2025)
Purpose – This research aims to develop SiapAjar as a teacher administration system designed to overcome the problem of teacher administration management that still uses traditional methods and to assess its feasibility.Methodology – The study employed a Research and Development (R&D) approach involving all 15 teachers from SD Negeri Sidomulyo 2 and SD Negeri Perdopo 02, along with three media experts. Data were gathered through Focus Group Discussions (FGDs) and questionnaires and then analyzed using descriptive quantitative methods to assess the application's design, functionality, and overall effectiveness.Findings – The results of this research are in the form of a teacher administration management application, SiapAjar, which can be accessed through web or mobile versions and includes features such as Effective Week Analysis, Annual Programs, Syllabus/Learning Objective Flow, Semester Programs, Lesson Plans, Teaching Journals, and Student Attendance Records. Validation of three experts shows an average score of 3.17 out of 4.00 on design, functionality, performance, and effectiveness, indicating the app is worth using. Meanwhile, users (teachers) gave an average score of 3.71 out of a scale of 4.00 for ease of use, efficiency and effectiveness, security and reliability, implementation support, and monitoring and evaluation, indicating that this application is feasible for teacher administration management.Significance—This study offers practical, efficient, user-friendly, and eco-friendly solutions for modernizing administration in educational institutions.Keywords: Management system, Teacher administration, SiapAjar